2017
DOI: 10.22302/iribb.jur.mp.v85i1.228
|View full text |Cite
|
Sign up to set email alerts
|

Perbaikan tanah melalui mediasi hayati [Bio-mediated soil improvement]

Abstract: AbstrakSifat tanah yang tidak mampu memberikan dukungan fisika-mekanis yang diperlukan seringkali menjadi kendala dalam pemanfaatannya baik untuk pertanian maupun konstruksi. Cara-cara yang umum adalah dengan aplikasi bahan kimia yang tidak saja mahal, tetapi juga tidak ramah lingkungan. Oleh karena itu diperlukan teknologi baru, berkelanjutan, dan inovatif untuk memperbaiki sifat-sifat mekanis tanah. Beberapa penelitian telah memberikan peluang untuk memanfaatkan mikroba untuk tujuan ini, khususnya mikroba ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Fortunately, using deliberate applications of controlledrelease fertilizers and slow-release fertilizers in specific circumstances where they are appropriate can accommodate timely plant nutrient demand requirements, maximize nutrient use efficiency, and minimize environmental concerns. In 1992, Goenadi [12,13,14,15] reported that slow release fertilizer is beneficial for estate crop seedlings (cocoa seedlings, oil palm seedlings, rubber seedlings) and showed the potential release period of the fertilizer is approximately 32 months. The newest technology in 2016 of an environment-friendly slow release fertilizer of zeolite-based nano-composite has been studied by Lateef et al [16].…”
Section: Chemical Compound Fertilizermentioning
confidence: 99%
“…Fortunately, using deliberate applications of controlledrelease fertilizers and slow-release fertilizers in specific circumstances where they are appropriate can accommodate timely plant nutrient demand requirements, maximize nutrient use efficiency, and minimize environmental concerns. In 1992, Goenadi [12,13,14,15] reported that slow release fertilizer is beneficial for estate crop seedlings (cocoa seedlings, oil palm seedlings, rubber seedlings) and showed the potential release period of the fertilizer is approximately 32 months. The newest technology in 2016 of an environment-friendly slow release fertilizer of zeolite-based nano-composite has been studied by Lateef et al [16].…”
Section: Chemical Compound Fertilizermentioning
confidence: 99%